Commutator structure of certain subgroups of the Shevale groups - Levchuk , V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Question 6.34 of the Kourov Notebook is solved: carry the familiar theorem of Merzlyakov on the joint commutator subgroup of covering subgroups over to Chevalley groups and moreover to orthogonal and unitary groups.